The Association Between Glucocorticoid Administration and the Risk of Impaired Efficacy of Axicabtagene Ciloleucel Treatment: A Systematic Review - Sun, Zhen; Xun, RenDe; Liu, MengSi; Wu, XiaoQin; Qu, HongTao (Frontiers in Immunology, 2021)
Background: Glucocorticoid is one of the common and important strategies for the treatment of chimeric antigen receptor T (CAR-T) cell therapy-related toxicity. However, there has been a theoretical concern about whether glucocorticoids use can impact the expansion of CAR-T cells and thus impair its efficacy. Hence, we reviewed studies related to the Axicabtagene ciloleucel (Axi-cel), a first-class and widely used CAR-T cell product, to elucidate the association between glucocorticoids administration and efficacy of Axi-cel. Method: We systematically searched PubMed, Embase, Web of Science, and Cochrane Library to identify studies of Axi-cel that used glucocorticoids as an intervention for the treatment of CAR-T cell-related adverse events and respectively evaluated any efficacy endpoints of intervention and controlled cohorts, published up to February 17, 2020. There were no restrictions on research type and language. Results: A total of 8 studies with 706 patients were identified in the systematic review. Except for one study found that high cumulative dose, prolonged duration and early use of glucocorticoids could shorten progression-free survival and/or overall survival, and another study that found a negative effect of glucocorticoids administration on overall survival in univariate analysis but disappeared in multivariate analysis, none of other studies observed a statistically significant association between glucocorticoids administration and progression-free survival, overall survival, complete response, and overall response rate. Conclusion: Our study indicated that the association between glucocorticoids therapy and the efficacy of CAR-T cell may be affected by cumulative dose, duration, and timing. There is currently no robust evidence that glucocorticoids can damage the efficacy of CAR-T cell, but the early use of glucocorticoids should be cautiously recommended.